1949
DOI: 10.1182/blood.v4.8.905.905
|View full text |Cite
|
Sign up to set email alerts
|

Iron Metabolism

Abstract: By determining the percentage utilization of intravenously administered radioiron for hemoglobin production over a period of two to three weeks, certain measurements of internal iron metabolism can be made. With a normal rate of blood production, changes in per cent utilization reflect alteration in iron stores. Iron depletion is characterized by more rapid and more complete utilization of radioiron. States of iron excess in hemochromatosis can be identified by their profound depression of radio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
11
0

Year Published

1953
1953
2002
2002

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(11 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…Iron balance is normally regulated by proximal intestinal mucosal absorption because there is no mechanism for its excretion (Finch and Huebers 1986). The mechanisms of regulation are poorly understood, but the control of iron uptake and transport by the intestine is probably primarily within the intestinal cell (Powell 1985).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Iron balance is normally regulated by proximal intestinal mucosal absorption because there is no mechanism for its excretion (Finch and Huebers 1986). The mechanisms of regulation are poorly understood, but the control of iron uptake and transport by the intestine is probably primarily within the intestinal cell (Powell 1985).…”
Section: Introductionmentioning
confidence: 99%
“…The mechanisms of regulation are poorly understood, but the control of iron uptake and transport by the intestine is probably primarily within the intestinal cell (Powell 1985). It is influenced by previous dietary exposure, amount of stored iron within the body and erythropoietic activity (Finch and Huebers 1986). The dietary iron requirement for horses has not been established, but is estimated to be -40 mg/kg of dry base diet (NRC 1989).…”
Section: Introductionmentioning
confidence: 99%
“…RE cells of the liver and the spleen play a central role in iron metabolism that goes beyond the simple iron storage function. They process Ͼ80% of the iron entering the plasma each day and thus represent a fundamental compartment in systemic iron metabolism (30). During pathophysiological states, such as chronic inflammation and anemia of chronic diseases (ACD), the role of RE cells of the macrophage lineage is pivotal in the systemic changes of iron metabolism leading, for instance, to hypoferremia, mainly through enhanced iron retention of circulating iron in RE cells (48).…”
mentioning
confidence: 99%
“…In this model, macrophages have a central role. It has been estimated that macrophages in vivo deliver 10,000,000 atoms of iron each minute to circulating Tf (30). The uptake of Fe 2ϩ Tf through TfR1 by macrophages may be the means for macrophages to be informed on the body iron status and erythroid demands.…”
mentioning
confidence: 99%
“…Previous investigators (8, 12, 13) have shown that there is no apparent loss or exchange of the isotopes of iron, nitrogen, or carbon when once incorporated into the hemoglobin molecule. However, radioiron is rapidly and almost completely reutflized following red cell breakdown unless suppressed by the competition of greatly increased body stores of non-radioactive iron and continuous high levels of non-radioactive total serum iron (7,14). N 15 incorporated in the protoporphyrin of heine and C14-tagged globin are supposedly not reutilized in the formation of new hemoglobin.…”
mentioning
confidence: 99%